2021
DOI: 10.3390/ijms22137192
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Understanding of Recent Developments in Bacterial Cellulose Biosynthesis at Genetic, Bioprocess and Product Levels

Abstract: Engineering biological processes has become a standard approach to produce various commercially valuable chemicals, therapeutics, and biomaterials. Among these products, bacterial cellulose represents major advances to biomedical and healthcare applications. In comparison to properties of plant cellulose, bacterial cellulose (BC) shows distinctive characteristics such as a high purity, high water retention, and biocompatibility. However, low product yield and extensive cultivation times have been the main chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 96 publications
0
23
0
Order By: Relevance
“…The multi-protein complex consists of individual enzymes, catalytic subunits, and regulatory proteins. The most recent proposed model for BC biosynthesis consists of sequential biochemical reactions well orchestrated by four key enzymatic biocatalysts that include (1) glucokinase that catalyses the phosphorylation of glucose to glucose-6-P, (2) phosphoglucomutase that catalyses the isomerisation of glucose-6-P to glucose-1-P, (3) UDPG pyrophosphorylase (UGPase) that synthesises UDP-glucose (UDPGlc), and (4) finally the cellulose synthase complex (BcsA, BcsB, BcsC, and BcsD) that links two UDPGlc monomers during polymerisation [ 23 , 24 ]. It was found that the UDPG pyrophosphorylase was the key player in the overall biosynthetic process [ 25 ].…”
Section: Biosynthesis Structure and Characteristics Of Bcmentioning
confidence: 99%
“…The multi-protein complex consists of individual enzymes, catalytic subunits, and regulatory proteins. The most recent proposed model for BC biosynthesis consists of sequential biochemical reactions well orchestrated by four key enzymatic biocatalysts that include (1) glucokinase that catalyses the phosphorylation of glucose to glucose-6-P, (2) phosphoglucomutase that catalyses the isomerisation of glucose-6-P to glucose-1-P, (3) UDPG pyrophosphorylase (UGPase) that synthesises UDP-glucose (UDPGlc), and (4) finally the cellulose synthase complex (BcsA, BcsB, BcsC, and BcsD) that links two UDPGlc monomers during polymerisation [ 23 , 24 ]. It was found that the UDPG pyrophosphorylase was the key player in the overall biosynthetic process [ 25 ].…”
Section: Biosynthesis Structure and Characteristics Of Bcmentioning
confidence: 99%
“…Together these genomic data provide a deeper insight into the polymer synthesis pathway that mainly engaged the BC synthase operons (bcs operon). This operon encoded the four essential cellulose synthesis genes, namely bcsA, bcsB, bcsC, and bcsD (Buldum and Mantalaris 2021;Liu et al 2018b). In addition, several regulating genes were also identified and located up and downstream from the cellulose synthase operons (Lu et al 2020;Singhania et al 2021).…”
Section: Bacterial Cellulose Producing Strainsmentioning
confidence: 99%
“…To reduce the production time, the cellulose synthase operon was heterogeneously expressed in E.coli, as a faster-growing host (Buldum et al 2018;Imai et al 2014). Though the BC production was detected in the early phase of the fermentation course (after 3 h), the resulted BC yield did not fulfill the expected commercial level (Buldum and Mantalaris 2021). More recent research has been directed toward the endogenous and heterologous expression of the cellulose regulating genes in the potent BC producing organisms (Jacek and Kubiak and et al 2019;Jacek and Ryngajłło et al 2019), with regards to cheaper and more available carbon sources, enhancing the oxygen assimilation under hypoxic conditions (Liu et al 2018a), or knocking-out the genes responsible for by-product accumulation (gluconic acid) during the fermentation course (Chun et al 2014), all causing an increase in BC productivity.…”
Section: Bacterial Cellulose Producing Strainsmentioning
confidence: 99%
“…In contrast to the cellulose synthesized by plants that accounts by far for the largest amount of cellulose processed by industry, BC is free of non-cellulosic polymers like lignin or hemicellulose (Cannon and Anderson 1991 ; Gullo et al 2018 ), while plant cellulose must be purified under costly and harsh chemical conditions (Saedi et al 2021 ). Especially acetic acid bacteria are well-known as high-level producers of microcrystalline cellulose, and this aspect was thoroughly studied (Abidi et al 2021 ; Buldum and Mantalaris 2021 ; Gullo et al 2018 ). The unique properties of high-water absorption and high tensile strength define the different applications of BC.…”
Section: Introductionmentioning
confidence: 99%